CONCEPTUAL PRINCIPLES AND PUBLIC ADMINISTRATION MECHANISMS OF FUNDING THE TRAINING OF HIGHER EDUCATION GRADUATES IN UKRAINE - Savchenko, I.; Chumak, O. (Pressing Problems of Public Administration, 2019)
The ongoing processes of reforming of the educational system in Ukraine are predetermined by the challenges of time, requirements of individuals obtaining higher education and integration processes to the world community. The purpose of this article is to determine the key principles of the perspective concept of the financing mechanism of the training of individuals obtaining higher education in Ukraine in accordance with the chosen reform vectors. The article outlines the existing problematic areas and shortcomings of financing of higher education funding, which determine the possible directions of its improvement through the mechanism of financial autonomy. The main changes in the legislation on higher education funding are envisaged, which are expected to be approved in the nearest future within the framework of reforms. To this end the experience of foreign countries on models of financing educational activities of higher educational institutions (mainly the USA and European countries) were studied. Based on this, the existing approaches to financing higher education in foreign countries are described, and the key funding levels which are expedient to be introduced in Ukraine are identified: sources of financing (state and local budgets, legal and private person’s funds, education loans and other sources) and scholarships. The necessity of financing education of individuals obtaining higher education is very actual according to the strategic tasks of the state in general, and the state educational strategy, in particular. The expediency of concluding a contract between the Ministry of Education and a higher education institution for the possibility of obtaining financing from the budget was proved. A three-component financing model for higher education is described: basic, performance-based financing, etc. The advantages of using this model in the national practice of financing higher education institutions are determined. The recommendations given in this article allow funding individuals obtaining higher education, taking into account the quality of educational services and fulfillment of its functions by the state.